Positive electrode material and battery
By jointly controlling the free nitrate and particle size, the high voltage performance of the positive electrode material is improved, and the structural distortion and cycle performance of the positive electrode material are solved, thereby improving structural stability and high voltage cycle stability performance.
Patent Information
- Application Number
- CN202411962916.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-04
AI Technical Summary
Existing positive electrode materials are prone to crystal structure distortion at high voltages, resulting in reduced capacity and cycling performance, and insufficient high voltage resistance.
By jointly controlling the mass content of free nitrate and the particle size distribution of the cathode material, it is ensured that the cathode material has a specific particle size distribution map and chemical formula, and improves its structural stability and lithium ion transport efficiency.
The structural stability of the positive electrode material at high voltage and the stability of the cycling performance of high voltage are improved, ensuring the optimization of capacity retention and cycling performance.
Smart Images

Figure CN119764399A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of positive electrode materials, and in particular relates to positive electrode materials and batteries. Background Art
[0002] Lithium-ion batteries are widely used in laptops, mobile phones, digital products and other fields due to their high energy density, good safety performance, long cycle life and environmental friendliness. The development of positive electrode materials is relatively slow compared to the development of large-capacity negative electrode materials (about 800-1000mAh / g). Therefore, researchers currently focus on developing large-capacity positive electrode materials to improve the energy density of lithium-ion batteries.
[0003] Under high voltage, excessive release of lithium ions from the positive electrode material causes the layered crystal structure to collapse, resulting in mixed cations and the release of lattice oxygen. The battery produces gas and the capacity and cycle performance of the positive electrode material decrease significantly. In addition, the side reaction between the positive electrode material and the electrolyte at high potential intensifies, producing carbon dioxide gas, which changes the surface crystal structure of the positive electrode material and causes the loss of lithium storage sites.
[0004] Therefore, how to improve the high voltage resistance of the positive electrode material and reduce the crystal structure distortion of the positive electrode material is one of the problems that need to be solved urgently. Summary of the invention
[0005] The purpose of the present application is to provide a positive electrode material and a battery. The positive electrode material of the present application has excellent high voltage resistance, can reduce the crystal structure distortion of the positive electrode material, and thus improve the structural stability and cycle performance of the positive electrode material.
[0006] In a first aspect, the present application provides a positive electrode material, wherein the mass content of free nitrate ions in the positive electrode material is Qppm, 10≤Q≤100; in the particle size number distribution spectrum of the positive electrode material, the positive electrode material has a first characteristic peak and a second characteristic peak, the first characteristic peak is located in the range of 0.1μm to 1μm and does not include 1μm, and the second characteristic peak is located in the range of 1μm to 4μm.
[0007] In some embodiments, the particle size distribution width of the second characteristic peak is Span(a), which satisfies 0.8<Span(a)<1.64;
[0008] In some embodiments, the particle size distribution width of the first characteristic peak is Span(b), which satisfies 0.4<Span(b)<0.8.
[0009] In some embodiments, the intensity ratio of the first characteristic peak to the second characteristic peak is ≥1.5.
[0010] In some embodiments, the volume particle size distribution of the positive electrode material satisfies: 1.0 μm ≤ Dv10 ≤ 2.5 μm, 3.0 μm ≤ Dv50 ≤ 4.5 μm, 5.5 μm ≤ Dv90 ≤ 10.0 μm.
[0011] In some embodiments, the chemical formula of the positive electrode material is Li n Ni x M y Mn z O2, wherein 0.9≤n<1.1, 0≤y<1, 0≤z<1, x+y+z=1, and y and z are not equal to 0 at the same time, wherein the M element includes at least one of Co, Al, Zr, Mg, W, Ti, Ba, Sr, Mg, Cr, Zn, V, Cu, Nb, Mo, Y and W.
[0012] In some embodiments, the mass content of free sulfate in the positive electrode material is K ppm, 10≤K≤800.
[0013] In some embodiments, the positive electrode material is a single crystal material, the positive electrode material includes crystal grains, and the grain size of the crystal grains is 1 μm to 5 μm.
[0014] In some embodiments, the specific surface area of the positive electrode material is 0.5 m 2 / g~1.5m 2 / g;
[0015] In some embodiments, the tap density of the positive electrode material is 1.0 g / cm 3 ~3.0g / cm 3 .
[0016] In some embodiments, the compaction density of the positive electrode material is 2.5 g / cm 3 ~3.5g / cm 3 .
[0017] In some embodiments, the bulk density of the positive electrode material is 0.5 g / cm 3 ~1.5g / cm 3 .
[0018] In some embodiments, the button-type battery made of the positive electrode material has a capacity retention rate of ≥95% after 50 cycles at a high voltage upper limit of 4.45V.
[0019] In a second aspect, the present application provides a battery, comprising a positive electrode material.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] The present application can improve the lattice distortion of the positive electrode material under high voltage state and enhance the lithium ion transmission efficiency by synergistically controlling the mass content of free nitrate ions and the particle size of the positive electrode material, so that the positive electrode material can have excellent high voltage resistance, structural stability and high voltage cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the embodiments of the present application or the technical solutions of the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0023] Figure 1 A schematic diagram of the discharge state of a battery provided in an embodiment of the present application.
[0024] Figure 2 This is the SEM spectrum of the positive electrode material oxide precursor prepared in Example 1 of the present application;
[0025] Figure 3 The XRD spectrum of the positive electrode material oxide precursor prepared in Example 1 of the present application;
[0026] Figure 4 This is the SEM spectrum of the positive electrode material prepared in Example 1 of the present application;
[0027] Figure 5 The particle size distribution spectrum of the positive electrode material prepared in Example 1 of the present application;
[0028] Figure 6 This is the XPS spectrum of the Li element on the surface of the positive electrode material prepared in Example 1 of the present application after charging and discharging for one week;
[0029] Figure 7 XRD spectrum of the positive electrode material oxide precursor prepared in Comparative Example 1 of the present application;
[0030] Figure 8 XPS spectrum of Li element on the surface of the positive electrode material prepared in Comparative Example 1 of the present application after one week of charge and discharge. DETAILED DESCRIPTION
[0031] In order to better understand the technical solution of the present application, the embodiments of the present application are described in detail below with reference to the accompanying drawings.
[0032] It should be clear that the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.
[0033] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features.
[0034] In order to easily understand the present invention, specific terms are appropriately defined in this application. Unless otherwise defined herein, scientific terms and technical terms used in the present invention have the meanings commonly understood by those skilled in the art to which the present invention belongs.
[0035] The present application provides a positive electrode material, wherein the mass content of free nitrate ions in the positive electrode material is Q ppm, 10≤Q≤100; in a particle size number distribution spectrum of the positive electrode material, the positive electrode material has a first characteristic peak and a second characteristic peak, the first characteristic peak is located in a range of 0.1 μm to 1 μm and does not include 1 μm, and the second characteristic peak is located in a range of 1 μm to 4 μm.
[0036] Therefore, the present application can improve the lattice distortion of the positive electrode material under high voltage state and improve the lithium ion transmission efficiency by synergistically controlling the mass content of free nitrate and the particle size distribution of the positive electrode material, so that the positive electrode material can have excellent high voltage resistance, structural stability and cycle stability. The mass content Qppm of the free nitrate of the positive electrode material satisfies 10≤Q≤100, and the positive electrode material has good structural stability and high voltage cycle performance. The inventor speculates that it is because the free nitrate of the positive electrode material can react with the active lithium ions to induce the formation of Li2O on the surface of the positive electrode material. Li2O has high voltage resistance, which helps to improve the high voltage resistance of the positive electrode material, and Li2O is distributed on the surface of the positive electrode material, which can reduce the surface energy of the positive electrode material, help to improve the crystal structure stability of the positive electrode material, and reduce oxygen escape in the lattice. However, due to the presence of Li2O on the surface of the positive electrode material, it will affect ion transmission, resulting in a decrease in the kinetics of lithium deintercalation reaction of the positive electrode material. Furthermore, by controlling the particle size of the positive electrode material, two different characteristic peaks are present in the particle size number distribution spectrum, which is beneficial to adjust the stacking mode of the monodisperse of the two particles and improve the stacking density of the positive electrode material particles. The tightly stacked particles can improve the transmission efficiency of lithium ions, reduce the impedance between particles, and improve the kinetics of lithium insertion and extraction reactions of the positive electrode material.
[0037] In some embodiments, the positive electrode material has the general chemical formula Li n Ni x M y Mn z O2, wherein 0.9≤n<1.1, 0≤y<1, 0≤z<1, x+y+z=1, and y and z are not equal to 0 at the same time, wherein M is a metal element.
[0038] Specifically, the value of n can be 0.90, 0.92, 0.95, 0.96, 0.98, 0.99, 1.0, 1.02, 1.05, 1.08 or 1.1, the value range of y can be 0, 0.001, 0.06, 0.1, 0.2, 0.28, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 0.99, and the value range of z can be 0, 0.001, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 0.99, and of course it can also be other values within the above range, which is not limited here.
[0039] Illustratively, the positive electrode material may be nickel-cobalt-manganese-lithium composite oxide, nickel-cobalt-aluminum-lithium composite oxide, nickel-cobalt-lithium composite oxide, nickel-manganese-lithium composite oxide, etc., which is not limited here.
[0040] In some embodiments, the metal element M includes at least one of Co, Al, Zr, Mg, W, Ti, Ba, Sr, Mg, Cr, Zn, V, Cu, Nb, Mo, Y and W. These doping elements can change the lattice constant of the positive electrode material or the valence state of the material bulk element, reduce cation mixing, improve the electronic conductivity and ionic conductivity of the positive electrode material, improve the stability of the material structure, and inhibit the collapse of the crystal structure of the positive electrode material, thereby improving the high voltage cycle performance of the positive electrode material.
[0041] In some embodiments, the particle size distribution width of the second characteristic peak in the particle size range of 1 μm to 4 μm is Span(a), which satisfies 0.8<Span(a)<1.64; Span(a) can specifically be 0.81, 0.85, 0.89, 0.92, 0.98, 1.01, 1.05, 1.2, 1.25, 1.3, 1.39, 1.4, 1.42, 1.45, 1.5, 1.57 or 1.63, etc., which are not limited here. Preferably, Span(a) satisfies 0.8<Span(a)<1.4.
[0042] In some embodiments, the particle size distribution width of particles with a particle size of 0.1 μm to 1 μm and excluding the first characteristic peak in the range of 1 μm is Span(b), which satisfies 0.4<Span(b)<0.8. Span(b) can specifically be 0.41, 0.42, 0.45, 0.58, 0.62, 0.7, 0.72, 0.75 or 0.795, etc., which is not limited here.
[0043] In some embodiments, the intensity ratio X of the first characteristic peak to the second characteristic peak is ≥ 1.5, indicating that the second characteristic peak in the positive electrode material is relatively shorter and more rounded, which conforms to the normal distribution, while the first characteristic peak is narrower and higher, indicating that the first characteristic peak is a narrow distribution width of particles in a micro-powder state, and the particle size of particles in a micro-powder state is relatively uniform. Exemplarily, the intensity ratio of the first characteristic peak to the second characteristic peak can be 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.3, 3.5, 4 or any value within the range formed by any two of the above values.
[0044] In some embodiments, the peak value percentage of the first characteristic peak is 0.15% to 0.2%. Specifically, it can be 0.15%, 0.16%, 0.17%, 0.18%, 0.19% or 0.20%. The peak value percentage of the second characteristic peak is 0.05% to 0.13%. Specifically, it can be 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.10%, 0.11%, 0.12% or 0.13%.
[0045] In some embodiments, the mass content of the free nitrate of the positive electrode material can specifically be 10ppm, 12ppm, 25ppm, 30ppm, 50ppm, 68ppm, 75ppm, 80ppm, 85ppm, 95ppm or 100ppm, etc., and of course it can also be other values within the above range, which are not limited here. When the mass content of the free nitrate of the positive electrode material is too high, too much Li2O will be formed on the surface of the positive electrode material, so that the ion transmission of the positive electrode material is blocked. When the mass content of the free nitrate of the positive electrode material is too low, the amount of Li2O formed on the surface of the positive electrode material is too small, the side reaction of the positive electrode material and the electrolyte is aggravated, especially under high voltage charge and discharge conditions, the capacity loss of the positive electrode material is aggravated. The present application controls the mass content of the free nitrate of the positive electrode material within the above range, which is beneficial to the positive electrode material having both high voltage resistance and excellent cycle stability and high capacity.
[0046] In some embodiments, the volume particle size distribution of the positive electrode material satisfies: 1.0 μm ≤ Dv10 ≤ 2.5 μm, 3.0 μm ≤ Dv50 ≤ 4.5 μm, 6.0 μm ≤ Dv90 ≤ 10.0 μm. Specifically, Dv10 may be 1.0 μm, 1.2 μm, 1.4 μm, 1.5 μm, 1.8 μm, 2.0 μm or 2.5 μm, etc., Dv50 may be 3.0 μm, 3.2 μm, 3.5 μm, 3.8 μm, 4.0 μm, 4.2 μm, 4.5 μm, etc., Dv90 may be 6.0 μm, 6.5 μm, 6.8 μm, 7.0 μm, 8.0 μm, 9.2 μm, 10.0 μm, etc., and of course, it may also be other values within the above range, which are not limited here. In the present application, controlling the volume particle size distribution of the positive electrode material to meet the above conditions can improve the compaction density of the positive electrode material and enhance the cycle stability of the positive electrode material.
[0047] In some embodiments, the mass content of free sulfate in the positive electrode material is K ppm, 10≤K≤800, specifically 10ppm, 50ppm, 80ppm, 100ppm, 150ppm, 200ppm, 275ppm, 400ppm, 470ppm, 560ppm, 650ppm, 780ppm or 800ppm, etc., and of course, other values within the above range are also possible, which are not limited here. Controlling the mass content of free sulfate within the above range can increase the migration rate of lithium ions, increase the capacity of the positive electrode material, and enhance the structural stability of the positive electrode material.
[0048] In some embodiments, the positive electrode material is a single crystal material, the positive electrode material includes crystal grains, the average grain size of the crystal grains is 1 μm to 5 μm, and the crystal grains are primary particles.
[0049] It should be specially pointed out that the "single crystal" known to those skilled in the art is not a "single crystal" in the strict sense. In crystallography, an ideal single crystal refers to a crystal with exactly the same arrangement and orientation. However, due to impurities, strain and crystal defects, ideal single crystals are very rare and difficult to produce in reality. Therefore, the materials known in the art that have a single crystal structure are actually more of a "single crystal-like morphology" positive electrode material, which only shows a single crystal-like large particle size in size, which is different from the polycrystalline particles composed of many small primary particles.
[0050] The grains with the same orientation in the present application can be a single particle composed of a primary particle. The above-mentioned single crystal positive electrode material can also contain a small amount of "quasi-secondary particles" formed by the adhesion of several single particles. "Primary particle" refers to the smallest particle unit identified when observing the positive electrode active material through a scanning electron microscope.
[0051] It should be noted that the difference between single crystal positive electrode materials and polycrystalline positive electrode materials (i.e., polycrystalline secondary particles) is that the smallest particle of polycrystalline secondary particles is a secondary particle formed by the agglomeration of nanometer-scale primary particles. For single crystal positive electrode materials, the smallest particle is usually a single primary particle of micrometer scale. Generally speaking, in addition to the EBSD test method, it is also possible to determine whether the obtained positive electrode product is a single crystal material by characterization methods such as scanning electron microscopy (SEM). For example, for single crystal positive electrode materials, the morphology of single crystal particles can be characterized by SEM, and it can be seen that the shape of single crystal particles is generally regular or irregular spherical, and there is no significant particle agglomeration. The orientation of single crystal positive electrode materials can also be characterized by EBSD. Through EBSD, it can be observed that the color in at least one grain is the same, so as to judge that the orientation in at least one grain is the same, and the grains with the same orientation are single crystals. It should be specifically noted that the "single crystal positive electrode material" known to those skilled in the art is not a "single crystal" in the strict crystallographic sense. In crystallography, an ideal single crystal refers to a crystal with completely the same arrangement and direction. However, due to impurities, strains and crystal defects, ideal single crystals are very rare and difficult to produce in the laboratory. Therefore, the single crystal cathode materials known in the art are actually more "single crystal morphology" cathode materials, which only show the size of large single crystal particles and are different from polycrystalline particles composed of many small primary particles.
[0052] In some embodiments, the average particle size of the crystal grains is 1 μm to 5 μm, and can be 1.0 μm, 1.2 μm, 1.4 μm, 1.5 μm, 1.8 μm, 2.0 μm, 2.4 μm, 2.8 μm, 3.0 μm, 3.5 μm, 3.8 μm, 4.0 μm, 4.2 μm, 4.5 μm, 4.8 μm or 5.0 μm, etc., and can be other values within the above range, which are not limited here. In the present application, controlling the particle size of the crystal grains within the above range can reduce the impedance of the positive electrode material, improve the lithium ion transmission efficiency, and help improve the capacity of the positive electrode material.
[0053] In some embodiments, the specific surface area of the positive electrode material is 0.5 m 2 / g~1.5m 2 / g; specifically, it can be 0.5m 2 / g, 0.6m 2 / g, 0.8m 2 / g, 1.0m 2 / g, 1.1m 2 / g, 1.2m 2 / g, 1.3m 2 / g, 1.4m 2 / g or 1.5m 2 / g, etc., and of course, it can also be other values within the above range, which is not limited here. By controlling the specific surface area of the positive electrode material within the above range, the positive electrode material can exhibit higher capacity, first coulombic efficiency, cycle stability and lower gas production.
[0054] In some embodiments, the tap density of the positive electrode material is 1.0 g / cm 3 ~3.0g / cm 3 , specifically 1.0 g / cm 3 , 1.2g / cm 3 , 1.3g / cm 3 , 1.4g / cm 3 , 1.5g / cm 3 , 1.6g / cm 3 , 1.7g / cm 3 , 1.8g / cm 3 , 1.9g / cm 3 , 2.0g / cm 3 , 2.1g / cm 3 , 2.2g / cm 3 , 2.4g / cm 3 , 2.5g / cm 3 , 2.8g / cm 3 or 3.0g / cm 3 Of course, it can be other values within the above range, which is not limited here. Controlling the tap density of the positive electrode material within the above range is conducive to improving the processing performance of the material and increasing the energy density of the battery.
[0055] In some embodiments, the compaction density of the positive electrode material is 2.5 g / cm 3 ~3.5g / cm 3 , specifically 2.5 g / cm 3 , 2.6g / cm 3 , 2.7g / cm 3 , 2.8g / cm 3 , 2.9g / cm 3 、3.0g / cm 3 、3.1g / cm 3 、3.2g / cm 3 、3.4g / cm 3 or 3.5g / cm 3 Of course, it can be other values within the above range, which is not limited here. Controlling the compaction density of the positive electrode material within the above range is beneficial to improving the energy density of the battery.
[0056] In some embodiments, the bulk density of the positive electrode material is 0.5 g / cm 3~1.5g / cm 3 , specifically 0.5 g / cm 3 , 0.6g / cm 3 , 0.7g / cm 3 , 0.8g / cm 3 , 0.9g / cm 3 , 1.0g / cm 3 , 1.1g / cm 3 , 1.2g / cm 3 , 1.4g / cm 3 or 1.5g / cm 3 Of course, it can be other values within the above range, which is not limited here. Controlling the bulk density of the positive electrode material within the above range is beneficial to improving the energy density of the battery.
[0057] In some embodiments, the button cell made of the positive electrode material has a capacity retention rate of ≥95% after 50 cycles of high voltage. Specifically, it can be 95%, 95.2%, 95.3%, 95.5%, 95.7%, 96.1%, 96.5%, 96.9%, 97.3%, 97.9% or 98.3%, etc. Of course, it can also be other values within the above range, which are not limited here. Preferably, the button cell made of the positive electrode material has a capacity retention rate of 95% to 97.3% after 50 cycles of high voltage. The capacity retention rate of the positive electrode material after 50 cycles of high voltage is within the above range, indicating that the positive electrode material has good high voltage resistance and cycle stability.
[0058] In a second aspect, the present application provides a method for preparing a positive electrode material, comprising the following steps:
[0059] S10, subjecting the hydroxide precursor of the positive electrode material to nitration annealing to obtain an oxide precursor containing nitrate ions.
[0060] S20, subjecting the mixture comprising the oxide precursor containing nitrate ions and the lithium source to a sintering treatment to obtain a primary sintering product; wherein the primary sintering treatment includes sequentially performing a first heating stage, a second heating stage, a first cooling stage and a third heating stage, the temperature of the first heating stage is 300°C to 600°C, the temperature of the second heating stage is 700°C to 1000°C, the temperature of the first cooling stage is 500°C to 700°C, and the temperature of the third heating stage is 720°C to 1000°C.
[0061] S30, gas-crushing and grading the primary sintered product to obtain a positive electrode material.
[0062] The preparation method of the positive electrode material provided in the present application is to subject the hydroxide precursor of the positive electrode material to nitration annealing treatment to obtain an oxide precursor containing nitrate ions. The mixture containing the oxide precursor containing nitrate ions and a lithium source is then subjected to a sintering treatment. The reactivity of the oxide precursor during the primary sintering process is lower than that of the hydroxide precursor. After multiple stages of heating and cooling treatment, it is conducive to the formation of single crystal particles in the positive electrode material. Finally, the primary sintering poor product is subjected to gas crushing and classification treatment to adjust the particle size of the particles, so that there are two different characteristic peaks in the particle size number distribution spectrum of the particles, so that the positive electrode material can have excellent high voltage resistance, structural stability and high voltage cycle stability.
[0063] The preparation method of the present application is described in detail below with reference to the examples:
[0064] Before step S10, the method further includes:
[0065] S01, preparing a salt solution of nickel, manganese and M elements into a mixed solution according to a certain stoichiometric ratio, adjusting the pH value of the mixed solution, and obtaining a hydroxide precursor of the positive electrode material by a coprecipitation method.
[0066] In some embodiments, the stoichiometric ratio of nickel, manganese and M element meets the following conditions: 0.5≤Ni<1, 0≤Mn<1, 0≤M<1, and M element includes at least one of Co, Al, Zr, Mg, W, Ti, Ba, Sr, Mg, Cr, Zn, V, Cu, Nb, Mo, Y and W. Wherein, Co and Mn are not 0 at the same time. Exemplarily, the molar ratio of Ni:Co:Mn can be 0.60:0.10:0.30, 0.67:0.05:0.28 or 0.90:0.5:0.05, etc.
[0067] In some embodiments, the salt solution is sulfate, specifically a mixed solution of sulfates of Ni, Co, Mn or Al. The sulfate radicals in the sulfate solution may be part of the source of sulfate radicals in the positive electrode material.
[0068] In some embodiments, the pH value of the mixed solution is 7 to 14, specifically 7, 7.5, 8, 8.5, 9, 9.5, 10, 11, 12, 13 or 14, etc., and of course it can also be other values within the above range, which is not limited here.
[0069] In some embodiments, the regulator used in the co-precipitation method can be ammonia water, citric acid, ethylene glycol, etc., so as to help the hydroxide in the mixed solution to be precipitated and separated from the mixed solution.
[0070] In other embodiments, a hydroxide precursor purchased from the market may also be used.
[0071] S10, subjecting the hydroxide precursor of the positive electrode material to nitration annealing to obtain an oxide precursor containing free nitrate.
[0072] In some embodiments, the nitration annealing treatment is performed after the annealing treatment is carried out in a mixed atmosphere containing nitric acid for a certain period of time.
[0073] In some embodiments, the volume concentration of nitric acid in the mixed atmosphere is 1% to 3%; specifically, it can be 1%, 1.5%, 2%, 2.5%, 2.8 or 3.0%, etc., and of course, it can also be other values within the above range, which is not limited here.
[0074] In some embodiments, the mass content of oxygen in the mixed atmosphere is <1.0 ppm. Too much oxygen will cause the oxide precursor grains to grow too fast, which is not conducive to maintaining the uniformity of the precursor particles and causes the reaction activity of the oxide precursor to decrease. In addition, controlling the oxygen content can also ensure that the mixed gas containing nitric acid will not be at risk of explosion.
[0075] In some embodiments, the mixed atmosphere includes nitric acid vapor and water vapor.
[0076] In some embodiments, the temperature of the nitration annealing treatment is 200°C to 800°C, specifically 200°C, 250°C, 300°C, 350°C, 480°C, 550°C, 600°C, 630°C, 650°C, 680°C, 700°C, 750°C, 780°C or 800°C, etc., and of course it can also be other values within the above range, which is not limited here.
[0077] In some embodiments, the heating rate of the nitration annealing treatment is 0.5°C / min to 3°C / min, specifically 0.5°C / min, 0.8°C / min, 1.0°C / min, 1.5°C / min, 1.8°C / min, 2.0°C / min, 2.5°C / min or 3.0°C / min, etc., and of course it can also be other values within the above range, which is not limited here.
[0078] In some embodiments, the holding time of the nitration annealing treatment is 3 h to 10 h, specifically 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h or 10 h, etc., and of course, it can also be other values within the above range, which is not limited here.
[0079] In some embodiments, the ambient pressure during the nitration annealing treatment is lower than the pressure of the mixed atmosphere.
[0080] In some embodiments, the ambient pressure during the nitration annealing treatment is 2.0 kPa to 4.0 kPa, specifically 2.0 kPa, 2.2 kPa, 2.5 kPa, 2.8 kPa, 3.0 kPa, 3.2 kPa, 3.5 kPa or 4.0 kPa, etc., and may be other values within the above range, which is not limited here.
[0081] In the present application, by controlling the process parameters such as the ambient pressure, holding time, and annealing temperature during the nitration annealing treatment, it is beneficial for the oxide precursor to form an appropriate amount of nitrate ions.
[0082] S20, performing a primary sintering treatment on the mixture of the oxide precursor containing nitrate ions and the lithium source to obtain a primary sintering product.
[0083] In some embodiments, the lithium source includes at least one of lithium hydroxide, lithium carbonate, lithium nitrate, lithium acetate, lithium sulfate and lithium oxalate. Preferably, the lithium salt is lithium carbonate.
[0084] In some embodiments, the amount of the lithium source and the oxide precursor added satisfies: the ratio of the molar amount of Li to the total molar amount of all metals in the oxide precursor is (0.87-1.25):1, specifically 0.87:1, 0.89:1, 0.92:1, 0.95:1, 0.98:1, 1.02:1, 1.05:1, 1.1:1, 1.17:1 or 1.25:1, etc., and of course, it can also be other values within the above range, which are not limited here. Within this range, the degree of Li / Ni cation mixing can be reduced, and the excessive residual lithium on the surface of the sintered product can be prevented from affecting the processing performance and safety performance.
[0085] In some embodiments, the oxide precursor is measured by XRD rays, and the oxide precursor has diffraction peaks at 35.4°±1° and 43.3°±1°, respectively. Among them, the diffraction peak at 35.4°±1° indicates that some particles in the oxide precursor have a rock salt phase, such as NiO with a rock salt phase; some particles have a spinel phase, such as NiMn2O4. The precursor particles of the rock salt phase are sintered to form particles with relatively large particle sizes, and the precursor particles of the spinel phase are sintered to form particles with relatively small particle sizes.
[0086] In some embodiments, the mixture further includes a dopant containing metal M, and the M element includes at least one of Zr, Mg, Ti, Ba, Sr, Cr, Zn, V, Cu, Nb, Mo, Y and W. Specifically, the dopant may contain a salt or oxide of metal M.
[0087] In some embodiments, the dopant includes at least one of Nb2O5, Nb2O3, MoO3, WO2, WO3, V2O5, V2O3, Sr(OH)2, SrO, SrCO3, TiO2, ZrO2, Zr(OH)4, Y2O3, BaO, Cr2O3, ZnO, CuO, Ta2O5, CaO, Sb2O3, Sb2O5, H3BO3, MgO and Mg(OH)2. Preferably, the dopant containing metal M is a compound of Zr or Ti.
[0088] In some embodiments, the mixing conditions for obtaining the mixture are: solid phase mixing at 10° C. to 50° C. for 0.3 h to 3 h.
[0089] In some embodiments, the temperature of solid phase mixing can be 10°C, 15°C, 20°C, 25°C, 30°C, 35°C, 40°C, 45°C or 50°C, and the time of solid phase mixing can be 0.3h, 0.4h, 0.5h, 0.6h, 0.8h, 1h, 1.5h, 1.8h, 2.5h or 3h, etc., and of course, it can also be other values within the above range, which are not limited here. Preferably, the temperature of solid phase mixing is 10°C to 35°C.
[0090] In some embodiments, the mixing device may be at least one of a ball mill, a three-dimensional mixer, a high-speed mixer, and a VC mixer.
[0091] In some embodiments, the primary sintering process includes sequentially performing a first heating stage, a second heating stage, a first cooling stage and a third heating stage, the temperature of the first heating stage is 300°C to 600°C, the temperature of the second heating stage is 700°C to 1000°C, the temperature of the first cooling stage is 500°C to 700°C, and the temperature of the third heating stage is 720°C to 1000°C.
[0092] In some embodiments, the temperature of the first heating stage can be 300°C, 350°C, 380°C, 400°C, 430°C, 450°C, 500°C, 550°C, 580°C or 600°C, etc. The time of the first heating stage is 3h to 5h, and can be 3h, 3.5h, 4h, 4.5h or 5h, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable. The temperature of the first heating stage is relatively low, and the lithium source can be fully melted and react with the oxide precursor.
[0093] In some embodiments, the heating rate in the first heating stage is 15°C / min to 20°C / min, specifically 15°C / min, 16°C / min, 17°C / min, 18°C / min, 19°C / min or 20°C / min, etc. Of course, it can also be other values within the above range, which is not limited here.
[0094] In some embodiments, the temperature of the second heating stage can be 700°C, 720°C, 770°C, 800°C, 880°C, 900°C or 1000°C, etc., but is not limited to the listed values, and other values not listed in the numerical range are also applicable. The time of the second heating stage is 4h to 12h, and can be 4h, 5h, 6h, 8h, 9h, 10h, 11h or 12h, etc., but is not limited to the listed values, and other values not listed in the numerical range are also applicable. The crystals of the positive electrode material are initially grown in the second heating stage, while reducing excessive growth of particles.
[0095] In some embodiments, the heating rate in the second heating stage is 0.5℃ / min to 3℃ / min, specifically 0.5℃ / min, 0.6℃ / min, 0.7℃ / min, 1.0℃ / min, 1.2℃ / min, 1.5℃ / min, 2.0℃ / min, 2.2℃ / min, 2.5℃ / min, 2.8℃ / min or 3℃ / min, etc. Of course, it can also be other values within the above range, which is not limited here.
[0096] In some embodiments, the temperature of the first cooling stage can be 500°C, 550°C, 580°C, 600°C, 620°C, 650°C, 680°C, 690°C or 700°C, etc., but is not limited to the listed values, and other values not listed in the numerical range are also applicable. The time of the first cooling stage is 2h to 6h, and can be 2h, 3h, 4h, 5h, 5.5h or 6h, etc., but is not limited to the listed values, and other values not listed in the numerical range are also applicable. The cooling process can rearrange the atoms on the surface of the grown primary particles to form a surface structure with lower free energy and higher chemical stability.
[0097] In some embodiments, the cooling rate in the first cooling stage is 0.5℃ / min to 3℃ / min, specifically 0.5℃ / min, 0.6℃ / min, 0.7℃ / min, 1.0℃ / min, 1.2℃ / min, 1.5℃ / min, 2.0℃ / min, 2.2℃ / min, 2.5℃ / min, 2.8℃ / min or 3℃ / min, etc., and of course it can also be other values within the above range, which is not limited here.
[0098] In some embodiments, the temperature of the third heating stage can be 720°C, 770°C, 800°C, 880°C, 900°C or 1000°C, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable. The time of the third heating stage is 1h to 3h, and can be 1h, 1.5h, 2h, 2.5h or 3h, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable. In this heating stage, the crystal structure of the primary particles of the positive electrode material is fully grown to ensure the structural stability of the primary particles.
[0099] In some embodiments, the heating rate of the third constant temperature stage is 0.5℃ / min to 3℃ / min, specifically 0.5℃ / min, 0.6℃ / min, 0.7℃ / min, 1.0℃ / min, 1.2℃ / min, 1.5℃ / min, 2.0℃ / min, 2.2℃ / min, 2.5℃ / min, 2.8℃ / min or 3℃ / min, etc., and of course it can also be other values within the above range, which is not limited here.
[0100] In some embodiments, the sintered product is cooled to room temperature after the third constant temperature stage.
[0101] In some embodiments, the primary sintering process is performed in an oxygen-containing atmosphere, and the oxygen content in the oxygen-containing atmosphere is ≥ 95%.
[0102] In some embodiments, when the dopant containing metal M is a compound of Zr or Ti, the temperature of the primary sintering treatment is 800° C. to 900° C., and the holding time is 8 h to 10 h.
[0103] S30, performing air flow crushing and classification on the primary sintering product to obtain a positive electrode material.
[0104] In some embodiments, the air pressure range of air flow milling is 0.3MPa to 0.6MPa. Optionally, the air pressure range of air flow milling can specifically be 0.3MPa, 0.4MPa, 0.5MPa and 0.6MPa, etc., or other values within the range. It can be selected according to actual needs and is not limited here.
[0105] In some embodiments, the volume particle size distribution of the product after air flow milling satisfies: 1.0 μm ≤ D V 10≤2.5μm, 3.0μm≤D V 50≤4.5μm, 5.5μm≤D V 90≤10.0μm.
[0106] In some embodiments, the frequency of the classification process is 80 Hz to 160 Hz. Optionally, the frequency of the classification process can be 80 Hz, 90 Hz, 100 Hz, 125 Hz, 140 Hz, 150 Hz, 160 Hz, etc., or other values within the range. The frequency can be selected according to actual needs and is not limited here. It is understandable that the classification frequency will affect the particle size after the gas crushing process.
[0107] In some embodiments, in the particle size distribution spectrum of the product after the classification treatment, the particle distribution curve in the particle size range of 1 μm to 4 μm has a peak that conforms to the Pulse function distribution, and the particle size distribution width of the particles in the particle size range of 1 μm to 4 μm is Span(a), which satisfies 0.8<Span(a)<1.64;
[0108] In some embodiments, in the particle size number distribution spectrum of the product after classification treatment, the particle distribution curve of particles with a particle size in the range of 0.1 μm to 1 μm but not including 1 μm has a peak that conforms to the Voigt function distribution, and the particle size distribution width of particles with a particle size in the range of 0.1 μm to 1 μm but not including 1 μm is Span(b), satisfying 0.4<Span(b)<0.8.
[0109] In some embodiments, the method further comprises: mixing the product after gas crushing and classification treatment with a coating agent containing metal M, and then performing a secondary sintering treatment to obtain a positive electrode material.
[0110] In some embodiments, the crushing method includes at least one of a double roller, a plowshare mixer / crusher, and a jet mill.
[0111] In some embodiments, the coating agent containing metal M, M is selected from at least one of Zr, Mg, Ti, Ba, Sr, Cr, Zn, V, Cu, Nb, Mo, Y and W. The coating agent containing metal M may be a salt or oxide of metal M. Preferably, the coating agent containing metal M includes a Nb compound and / or a W compound.
[0112] In some embodiments, the secondary sintering process is performed in an oxygen-containing atmosphere, and the oxygen content in the oxygen-containing atmosphere is ≥ 95%.
[0113] In some embodiments, the temperature of the secondary sintering treatment is 300°C to 800°C, specifically 300°C, 320°C, 330°C, 350°C, 380°C, 400°C, 450°C, 500°C, 550°C, 650°C, 700°C or 800°C, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0114] In some embodiments, the holding time of the secondary sintering treatment is 6h to 24h, specifically 6h, 8h, 10h, 12h, 15h, 18h or 24h, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0115] In some embodiments, when the coating agent containing metal M includes a Nb compound and / or a W compound, the temperature of the secondary sintering treatment is 500° C. to 600° C., and the holding time of the secondary sintering treatment is 6 h to 8 h.
[0116] In a third aspect, the present application provides a battery, the battery comprising the positive electrode material of the first aspect or the positive electrode material prepared according to the preparation method of the positive electrode material.
[0117] The battery provided in the present application may be a secondary battery (such as a lithium-ion battery, a sodium-ion battery, etc.), including a housing, an electrode assembly, and an electrolyte. The electrode assembly and the electrolyte are both located in the housing. The housing may be a packaging bag encapsulated by an encapsulation film (such as an aluminum-plastic film), such as a soft-pack battery.
[0118] In other embodiments, the secondary battery may also be a steel shell battery, an aluminum shell battery, etc.
[0119] Figure 1 A schematic diagram of the discharge state of a battery provided in an embodiment of the present application, such as Figure 1 As shown, the battery includes a shell and an electrode assembly, the electrode assembly includes a positive electrode sheet 1, a negative electrode sheet 2 and a separator 3, and the separator 3 is arranged between the positive electrode sheet 1 and the negative electrode sheet 2. The electrode assembly can be a laminated structure, which is formed by alternately stacking the positive electrode sheet 1, the separator 3 and the negative electrode sheet 2 in sequence.
[0120] In other embodiments, the electrode assembly may also be a winding structure, which is formed by stacking a positive electrode sheet, a separator, and a negative electrode sheet in sequence and then winding them.
[0121] In some embodiments, the positive electrode sheet 1 includes a positive electrode current collector 11 and a positive electrode active material layer 12 disposed on at least one surface of the positive electrode current collector 11 .
[0122] In some embodiments, the positive electrode current collector 11 may be aluminum foil or nickel foil, or any composite current collector disclosed in the prior art, such as but not limited to the current collector formed by combining the aforementioned conductive foil (aluminum foil or nickel foil, etc.) and a polymer substrate. The positive electrode active material layer 12 comprises a positive electrode active material, a conductive agent, and a binder, wherein the positive electrode active material is the positive electrode material of the first aspect described above or a positive electrode material prepared according to the preparation method of the positive electrode material described above.
[0123] In some embodiments, the negative electrode sheet 2 includes a negative electrode current collector 21 and a negative electrode active material layer 22 disposed on at least one surface of the negative electrode current collector.
[0124] In some embodiments, the negative electrode current collector 21 can be made of at least one of copper foil, nickel foil, stainless steel foil, titanium foil or a carbon-based current collector, or can be any composite current collector disclosed in the prior art, such as but not limited to a current collector formed by combining the aforementioned conductive foil and a polymer substrate.
[0125] In some embodiments, the negative electrode active material layer 22 includes a negative electrode material, and the negative electrode material includes but is not limited to artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material can be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material can be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries can also be used. These negative electrode active materials can be used alone or in combination of two or more.
[0126] The battery provided in the embodiment of the present application has the advantages of high capacity, high initial efficiency, long cycle life, excellent rate performance and low expansion. The battery can be a lithium ion battery, a sodium ion battery, a solid electrolyte battery, etc., which is not limited here.
[0127] The following is a further description of the embodiments of the present invention in multiple embodiments. The embodiments of the present invention are not limited to the following specific embodiments. The embodiments can be appropriately modified within the scope of the unchanged main rights.
[0128] Test method:
[0129] (1) Testing of free anions of positive electrode materials
[0130] Weigh about 0.7 g of sample into a 70 mL beaker, accurate to 0.0001 g;
[0131] Accurately measure 50mL of ultrapure water in a 50mL volumetric flask, first add a small amount of ultrapure water (about 7mL) to the sample, stir evenly with a glass rod, then add the remaining ultrapure water, stir evenly, ultrasonicate for 3 minutes, and let stand for about 17 minutes to allow the sample to precipitate;
[0132] Use a 1mL sterile syringe to draw the sample supernatant, inject it into the instrument through a disposable filter head for testing; ion chromatograph model: Thermo Scientific Dionex ICS-6000; chromatographic setting conditions: eluent concentration: 25mmol / L; eluent flow rate: 0.3mL / min; column temperature: 30±1℃; detection cell temperature: 35±1℃; suppressor current: 26mA; chromatographic column: anion exchange column (4*250mm, AS11-HC); data acquisition: after the baseline is stable (the signal value change is less than 0.1μS / 20min), click data acquisition and the analysis will begin.
[0133] Result calculation: The calculation formula is Q = Ci * V / M, where Q is the content of element i in the sample, mg / kg; Ci is the concentration of element i in the sample solution, mg / L; V is the volume of the sample solution, ml; M is the mass of the sample, g. In the anion test, by measuring the content of N element, it can be converted into nitrate NO3 by ion molecular weight. - The content of the element S can be converted into sulfate SO4 by the molecular weight of the ion by testing the content of the element S. 2- The content.
[0134] (2) Mastersizers 3000 were used to characterize the particle size distribution and volume distribution of the positive electrode material. The specific method is as follows:
[0135] The particle size test method refers to GB / T 19077-2016. It can be conveniently measured using a laser particle size analyzer, such as the Mastersizer 3000 laser particle size analyzer from Malvern Instruments Ltd., UK.
[0136] In the particle size distribution spectrum of the positive electrode material, the particle size distribution width functions Span(a) and Span(b) of the two peaks are expressed as:
[0137]
[0138] D90 p1 、D10 p1 、D50 p1 They are the particle size ratio parameters of the second characteristic peak with x in the range of 1 μm-4 μm;
[0139]
[0140] D90 p2 、D10 p2 、D50 p2 They are the particle size number ratio parameters of the first characteristic peak in the range of 0.1μm-1μm.
[0141] The volume-based cumulative particle size distribution can be conveniently determined using a laser particle size analyzer, such as the Mastersizer 3000 laser particle size analyzer from Malvern Instruments Ltd. Dv10 represents the particle size corresponding to 10% of the cumulative particle size distribution, Dv50 represents the particle size corresponding to 50% of the cumulative particle size distribution, and Dv90 represents the particle size corresponding to 90% of the cumulative particle size distribution.
[0142] (3) Testing method for specific surface area of positive electrode materials:
[0143] The specific surface area of the positive electrode material was tested using a Micromeritics Tristar 3020 specific surface area and pore size analyzer. A certain mass of powder was weighed and completely degassed under vacuum heating to remove the surface adsorbent. The specific surface area of the particles was calculated using the nitrogen adsorption method based on the amount of nitrogen adsorbed. The unit is m 2 / g.
[0144] (4) Kanta tap density test of positive electrode material:
[0145] Using the American Quantacon tap density tester (model: DAT-4-220), the steps are as follows:
[0146] 1. Clean the measuring cylinder and weigh the mass of the measuring cylinder as m1;
[0147] 2. Add about 50g of sample into the measuring cylinder, try to make the sample surface level, and wipe the surrounding area with a paper towel;
[0148] 3. Weigh the total mass of the sample and the measuring cylinder to be m2;
[0149] 4. Place the measuring cylinder on the vibration table and fix it with three symmetrical fixing feet;
[0150] 5. Turn on the instrument and set the vibration times to 5000 times; turn on the vibration switch, and the instrument will automatically stop after vibrating to the specified times;
[0151] 6. Take out the measuring cylinder and read the volume of the sample. If the sample surface is horizontal after tapping, read the volume directly; if it is a slanted line, take the average value V of the readings at the highest and lowest points; tap density = (m2-m1) / V.
[0152] (5) Compacted density test of positive electrode materials:
[0153] The compaction density of the positive electrode material is tested using the American carver 4350, and the steps are as follows: weigh 1g of sample and put it into a mold and press it with a pressure of 3T for 30s. After pressing, the height is tested to calculate the compaction.
[0154] (6) Bulk density test of positive electrode material:
[0155] The compacted density of the positive electrode material is tested using a loose density meter BT101, and the steps are as follows: take an appropriate amount of sample, let it flow naturally into the distribution box, alternately pass through four glass plates with an inclined angle of 25° and a square funnel in the distribution box, and flow into a cylindrical cup with a known volume (25 ml), and finally weigh the mass of the powder in the cylindrical cup.
[0156] (7) IPC test method for positive electrode materials:
[0157] Take 0.3g of the sample to be tested and dissolve it in aqua regia, cool and dilute to a volume of 100ml to prepare the mother solution for determination; take 1mL of the mother solution for determination, dilute it 100 times, and test the content of the main elements Li, Ni, Co, and Mn and the content of other elements such as doping elements by ICP. The determination is carried out using Agilent 5110ICP-OES detection equipment.
[0158] (8) Test on average particle size of positive electrode material:
[0159] Hitachi S4800 scanning electron microscope was used to take 5 views of samples at different positions at 3000 times magnification. Nano Measure software was used to measure the primary particle size of the positive electrode material in the view, and the average value of the 5 primary particle sizes was taken as the particle size of the grain.
[0160] (9) Electrochemical performance test:
[0161] a. Preparation of electrochemical performance test samples:
[0162] Button battery production:
[0163] Ingredients: NCM:SP:5% PVDF glue = 93:5:2 = 9.3g:0.5g:4.0g, NMP = 9g, stir at high speed to disperse evenly.
[0164] Coating and drying: evenly coat the slurry on 20μm thick aluminum foil with a 210um coater, set the coating length to the maximum length of the coater, cut the back half of the electrode and put it into a 100℃ forced drying oven to dry for more than 1.5 hours.
[0165] Rolling, punching and drying: When rolling, adjust the roller machine to 1 roller gap and roll 3 times; use a 14mm punching machine to punch holes, weigh, and place in a vacuum drying oven for vacuum drying at 85°C for more than 8 hours.
[0166] Button battery (LIR2016) assembly: positive electrode shell - 2 drops of electrolyte - positive electrode sheet (14mm) - 3 drops of electrolyte - 20μm separator - 2 drops of electrolyte Lithium sheet-150μm nickel foam-negative electrode shell (dried at 50℃), after the battery is assembled, it is sealed and taken out of the glove box for testing.
[0167] b. Power-off test:
[0168] After standing for 12 hours, perform the battery test according to the following system:
[0169] After 2 weeks of 0.1C charge and 0.1C discharge, the charge cut-off voltage was 4.45V, the discharge cut-off voltage was 2.5V, and the constant voltage cut-off current was 0.005C. The first cycle capacity, discharge specific capacity and first coulombic efficiency were measured.
[0170] When charging at 0.5C and discharging at 1C, with a charging cut-off voltage of 4.45V and a discharging cut-off voltage of 2.5V, 50 cycles were performed with a constant voltage cut-off current of 0.05C. The ratio of the measured capacity to the first cycle capacity is the 50-cycle high voltage cycle capacity retention rate.
[0171] The test results are shown in Table 1.
[0172] Example 1
[0173] (1) Dissolve metal nickel, metal manganese and metal cobalt in sulfuric acid to form a sulfate solution; prepare the three solutions according to the stoichiometric ratio of Ni:Co:Mn=60:10:30 to form a mixed solution with a total concentration of Ni, Co and Mn of 2 mol / L. Continuously introduce 1 mol / L NaOH solution and 0.5 mol / L ammonia water into the mixed solution to control the pH value within the range of 11±0.2. V When the particle size reaches 8 μm, the reaction is stopped, and the precipitate is centrifuged, washed and dried to obtain the positive electrode material hydroxide precursor.
[0174] (2) The positive electrode material hydroxide precursor is placed in an atmosphere with a nitric acid concentration of 2% for nitration annealing; the atmosphere contains only HNO3 and H2O, and the O2 content is <1.0ppm; the temperature is heated to 600°C at a heating rate of 2°C / min and kept at this temperature for 6 hours for annealing; during the annealing process, the pressure of the reaction environment is controlled at 3.0kPa to obtain an oxide precursor. The general chemical formula of the positive electrode material oxide precursor is Ni 0.6 Co 0.1 Mn 0.3 O x (The content deviation of each element is within ±1%). Figure 2 This is the SEM spectrum of the positive electrode material oxide precursor prepared in Example 1 of the present application, Figure 3 The XRD pattern of the positive electrode material oxide precursor prepared in Example 1 of the present application; Figure 2 and Figure 3As shown, there is a characteristic peak of the oxide precursor within the range of ±1° at 35.4° and 43.3°.
[0175] (3) The oxide precursor is mixed with Li2CO3 at a Li / Me (Me is the sum of Ni, Co, and Mn) molar ratio of 1.02:1, and ZrO2 with a mass content of 2000 ppm relative to the oxide precursor is added, and the mixture is placed in an atmosphere electric heating furnace or a Joule heat reactor, using an oxygen atmosphere and controlling the reaction gas pressure at 10 Pa for a primary sintering treatment; the primary sintering treatment includes heating from room temperature to 500°C at a heating rate of 20°C / min, and the holding time of the first heating stage is 4 hours; the second heating stage is carried out at a heating rate of 2°C / min to a temperature of 700°C and the holding time is 6 hours; the first cooling stage is carried out at a cooling rate of 1°C / min to a temperature of 500°C and the holding time is 4 hours; the third heating stage is carried out at a heating rate of 1°C / min to a temperature of 900°C and the holding time is 2 hours; the fourth platform temperature is cooled at a cooling rate of 2°C / min to obtain a primary sintering product.
[0176] (4) The primary sintered product is subjected to air flow milling. The air pressure of the air flow milling is controlled at 0.55 MPa, and the frequency of the grading treatment is controlled at 120 Hz. The volume distribution particle size Dv10 of the obtained matrix material is 1.86 μm, Dv50 is 3.73 μm, and Dv90 is 7.62 μm.
[0177] (5) The matrix material was mixed with 1000 ppm of Nb2O5 and secondary sintered at 500°C for 6 h in an oxygen atmosphere to obtain a positive electrode material.
[0178] The positive electrode material prepared in Example 1 of the present application is Li 1.02 Ni 0.6 Co 0.1 Mn 0.297 Zr 0.002 Nb 0.001 O2, Figure 4 This is the SEM spectrum of the positive electrode material prepared in Example 1 of the present application. Figure 5 This is the particle size distribution spectrum of the positive electrode material prepared in Example 1 of the present application; Figure 4 and Figure 5 As shown in the figure, the positive electrode material particles are dispersed, and there are two characteristic peaks in the particle size distribution spectrum. After the positive electrode material is loaded into the battery and charged and discharged for one week, Figure 6 This is the XPS spectrum of the Li element on the surface of the positive electrode material prepared in Example 1 of the present application after charging and discharging for one week, as shown in Figure 6 As shown, there are more Li2O phases on the surface of the positive electrode material, which is beneficial to the cycle stability of the positive electrode material.
[0179] Example 2
[0180] (1) Dissolve metal nickel, metal manganese and metal cobalt in sulfuric acid to form a sulfate solution; prepare the three solutions according to the stoichiometric ratio of Ni:Co:Mn=67:5:28 to form a mixed solution with a total concentration of Ni, Co and Mn of 2 mol / L. Add appropriate amounts of citric acid and ethylene glycol to the mixed solution, control the pH value within the range of 8-10, and then place it in a reactor and keep it at 180°C for 24 hours to obtain a precipitate, which is centrifuged, washed and dried to obtain a positive electrode material hydroxide precursor.
[0181] (2) placing the positive electrode material hydroxide precursor in an atmosphere with a nitric acid concentration of 2% for nitration annealing; the atmosphere contains only HNO3 and H2O, and the O2 content is less than 1.0 ppm; heating to a temperature of 600°C at a heating rate of 2°C / min, and annealing is performed for 6 hours; during the annealing process, the pressure of the reaction environment is controlled at 3.0 kPa to obtain an oxide precursor, and the chemical formula of the positive electrode material oxide precursor is Ni 0.67 Co 0.05 Mn 0.28 O x (The content deviation of each element is within ±1%).
[0182] (3) The oxide precursor is mixed with Li2CO3 at a Li / Me (Me is the sum of Ni, Co, and Mn) molar ratio of 1.01:1, and TiO2 is added with a mass content of 1000 ppm relative to the oxide precursor. The subsequent sintering process is the same as step (3) of Example 1.
[0183] (4) The primary sintered product is subjected to air flow milling. The air pressure of the air flow milling is controlled at 0.4 MPa and the classification frequency is controlled at 130 Hz. The volume distribution particle size Dv10 of the obtained matrix material is 1.67 μm, Dv50 is 3.58 μm, and Dv90 is 6.89 μm.
[0184] (5) The base material was crushed and mixed with 1500 ppm of Al2O3, and then secondary sintered at 500°C for 6 h in an oxygen atmosphere to obtain a positive electrode material.
[0185] Example 3
[0186] The difference from Example 1 is:
[0187] (2) placing the positive electrode material hydroxide precursor in an atmosphere with a nitric acid concentration of 3% for nitration annealing; the atmosphere contains only HNO3 and H2O, and the O2 content is less than 1.0 ppm; heating to a temperature of 200°C at a heating rate of 3°C / min, and annealing is performed for 3 hours; during the annealing process, the pressure of the reaction environment is controlled at 2.0 kPa to obtain an oxide precursor, whose general chemical formula is Ni0.6 Co 0.1 Mn 0.3 O x (The content deviation of each element is within ±1%).
[0188] Example 4
[0189] The difference from Example 1 is:
[0190] (3) The oxide precursor is mixed with Li2CO3 at a Li / Me (Me is the sum of Ni, Co, and Mn) molar ratio of 1.02:1, and ZrO2 with a mass content of 2000 ppm relative to the oxide precursor is added, and the mixture is placed in an atmosphere electric heating furnace or a Joule heat reactor, using an oxygen atmosphere and controlling the reaction gas pressure at 10 Pa for a primary sintering treatment; the primary sintering treatment includes heating from room temperature to 300°C at a heating rate of 20°C / min, and the holding time of the first heating stage is 5 hours; the second heating stage is carried out at a heating rate of 2°C / min to a temperature of 900°C and the holding time is 4 hours; the first cooling stage is carried out at a cooling rate of 1°C / min to a temperature of 600°C and the holding time is 6 hours; the third heating stage is carried out at a heating rate of 0.5°C / min to a temperature of 700°C and the holding time is 6 hours; the fourth platform temperature is cooled at a cooling rate of 1°C / min to obtain a primary sintering product.
[0191] Example 5
[0192] (1) Dissolve metal nickel, metal manganese and metal cobalt in nitric acid to form a nitrate solution; prepare the three solutions according to the stoichiometric ratio of Ni:Co:Mn=90:5:5 to form a mixed solution with a total concentration of Ni, Co and Mn of 2 mol / L. Add appropriate amounts of citric acid and ethylene glycol to the mixed solution, control the pH value within the range of 7-9, and then place it in a reactor and keep it at 180°C for 24 hours to obtain a precipitate, which is centrifuged, washed and dried to obtain a positive electrode material hydroxide precursor.
[0193] (2) The positive electrode material hydroxide precursor is placed in an atmosphere with a nitric acid concentration of 1% for nitration annealing; the atmosphere contains only HNO3 and H2O, and the O2 content is <1.0ppm; the temperature is heated to 800°C at a heating rate of 0.5°C / min and kept at this temperature for 10 hours for annealing; during the annealing process, the pressure of the reaction environment is controlled at 2.0kPa to obtain an oxide precursor, whose general chemical formula is Ni 0.9 Co 0.05 Mn 0.05 O x (The content deviation of each element is within ±1%).
[0194] (3) The oxide precursor is mixed with Li2CO3 at a Li / Me (Me is the sum of Ni, Co, and Mn) molar ratio of 1.02:1, and ZrO2 with a mass content of 2000 ppm relative to the oxide precursor is added, and the mixture is placed in an atmosphere electric heating furnace or a Joule heat reactor, using an oxygen atmosphere and controlling the reaction gas pressure at 10 Pa for a primary sintering treatment; the primary sintering treatment includes heating from room temperature to 300°C at a heating rate of 20°C / min, and the holding time of the first heating stage is 5 hours; the second heating stage is carried out at a heating rate of 2°C / min to a temperature of 800°C and the holding time is 4 hours; the first cooling stage is carried out at a cooling rate of 1°C / min to a temperature of 500°C and the holding time is 6 hours; the third heating stage is carried out at a heating rate of 0.5°C / min to a temperature of 600°C and the holding time is 6 hours; the fourth platform temperature is cooled at a cooling rate of 1°C / min to obtain a primary sintering product.
[0195] (4) The primary sintered product is subjected to air flow milling. The air pressure of the air flow milling is controlled at 0.55 MPa, and the frequency of the grading treatment is controlled at 120 Hz. The volume distribution particle size Dv10 of the obtained matrix material is 1.86 μm, Dv50 is 3.73 μm, and Dv90 is 7.62 μm.
[0196] (5) The matrix material was mixed with 1000 ppm of Nb2O5 and secondary sintered at 500°C for 6 h in an oxygen atmosphere to obtain a positive electrode material.
[0197] Example 6
[0198] The difference from Example 4 is that:
[0199] (3) The oxide precursor is mixed with Li2CO3 at a Li / Me (Me is the sum of Ni, Co, and Mn) molar ratio of 0.99:1, and ZrO2 with a mass content of 2000 ppm relative to the oxide precursor is added, and the mixture is placed in an atmosphere electric heating furnace or a Joule heat reactor, using an oxygen atmosphere and controlling the reaction gas pressure at 10 Pa for a primary sintering treatment; the primary sintering treatment includes heating from room temperature to 300°C at a heating rate of 20°C / min, and the holding time of the first heating stage is 5 hours; the second heating stage is carried out at a heating rate of 2°C / min to a temperature of 900°C and the holding time is 4 hours; the first cooling stage is carried out at a cooling rate of 1°C / min to a temperature of 600°C and the holding time is 6 hours; the third heating stage is carried out at a heating rate of 0.5°C / min to a temperature of 700°C and the holding time is 6 hours; the fourth platform temperature is cooled at a cooling rate of 1°C / min to obtain a primary sintering product.
[0200] Example 7
[0201] The difference from Example 4 is that:
[0202] (1) Dissolving metallic nickel, metallic manganese, and metallic cobalt in nitric acid respectively to form nitrate solutions; and preparing the three solutions into a mixed solution having a total concentration of Ni, Co, and Mn of 2 mol / L according to a stoichiometric ratio of Ni:Co:Mn=83:11:06.
[0203] Example 8
[0204] The difference from Example 4 is that:
[0205] (1) Dissolving metallic nickel, metallic manganese, and metallic cobalt in sulfuric acid respectively to form a sulfate solution; and configuring the three solutions into a mixed solution having a total concentration of Ni, Co, and Mn of 2 mol / L according to a stoichiometric ratio of Ni:Co:Mn=70:10:20.
[0206] Example 9
[0207] The difference from Example 4 is that:
[0208] (1) Dissolving metallic nickel and metallic cobalt in sulfuric acid respectively to form a sulfate solution; and configuring the two solutions into a mixed solution having a total concentration of Ni and Co of 2 mol / L according to a stoichiometric ratio of Ni:Co=90:10.
[0209] Example 10
[0210] The difference from Example 4 is that:
[0211] (1) Dissolving metallic nickel and metallic manganese in sulfuric acid respectively to form a sulfate solution; and configuring the two solutions into a mixed solution having a total Ni and Mn concentration of 2 mol / L according to a stoichiometric ratio of Ni:Mn=90:10.
[0212] Embodiment 11
[0213] The difference from Example 2 is that:
[0214] (2) The positive electrode material hydroxide precursor is placed in an atmosphere with a nitric acid concentration of 2% for nitration annealing; the atmosphere contains only HNO3 and H2O, and the O2 content is <1.0ppm; the temperature is heated to 400°C at a heating rate of 2°C / min and kept at this temperature for 3 hours for annealing; during the annealing process, the pressure of the reaction environment is controlled at 3.0kPa to obtain an oxide precursor with a general chemical formula of Ni 0.67 Co 0.05 Mn 0.28 O x (The content deviation of each element is within ±1%).
[0215] Example 12
[0216] The difference from Example 1 is:
[0217] (4) The primary sintered product is subjected to air flow milling. The air pressure of the air flow milling is controlled at 0.35 MPa, and the frequency of the grading treatment is controlled at 60 Hz. The volume distribution particle size Dv10 of the obtained matrix material is 2.23 μm, Dv50 is 4.42 μm, and Dv90 is 8.87 μm.
[0218] Example 13
[0219] The difference from Example 1 is:
[0220] (1) Dissolve metal nickel, metal cobalt, and metal aluminum in sulfuric acid to form a sulfate solution; prepare the three solutions according to the stoichiometric ratio of Ni:Co:Al=80:15:5 to form a mixed solution with a total concentration of Ni, Co, and Al of 2 mol / L. Continuously introduce a 1 mol / L NaOH solution and a 0.5 mol / L ammonia solution into the mixed solution to control the pH value within the range of 10.8 to 11.2. V When the particle size reaches 8 μm, the reaction is stopped, and the precipitate is centrifuged, washed and dried to obtain the positive electrode material hydroxide precursor.
[0221] Embodiment 14
[0222] The difference from Example 1 is:
[0223] (4) The primary sintered product is subjected to air flow milling. The air pressure of the air flow milling is controlled at 0.5 MPa and the classification frequency is controlled at 170 Hz. The volume distribution particle size Dv10 of the obtained matrix material is 0.86 μm, Dv50 is 2.73 μm, and Dv90 is 5.62 μm.
[0224] Embodiment 15
[0225] The difference from Example 1 is:
[0226] (4) The primary sintered product is subjected to air flow milling. The air pressure of the air flow milling is controlled at 0.25 MPa and the classification frequency is controlled at 70 Hz. The volume distribution particle size Dv10 of the obtained matrix material is 2.66 μm, Dv50 is 4.95 μm, and Dv90 is 9.83 μm.
[0227] Comparative Example 1
[0228] The difference from Example 1 is:
[0229] (2) The positive electrode material hydroxide precursor Ni 0.6 Co 0.1 Mn 0.3 (OH) x The temperature was heated to 200°C at a heating rate of 3°C / min and annealed for 3 h to obtain an oxide precursor with the general chemical formula of Ni0.6 Co 0.1 Mn 0.3 O x (The content deviation of each element is within ±1%), and the XRD results are as follows Figure 7 shown.
[0230] The positive electrode material prepared in this comparative example does not contain free nitrate because it has not been subjected to nitration treatment. After the positive electrode material is loaded into a battery and charged and discharged for one week, Figure 8 The XPS spectrum of the Li element on the surface of the positive electrode material prepared in Comparative Example 1 of the present application after one week of charge and discharge is as follows: Figure 8 As shown, there is only a small amount of Li2O phase on the surface of the positive electrode material, which is not conducive to the cycle stability of the positive electrode material.
[0231] Comparative Example 2
[0232] The difference from Example 5 is:
[0233] (2) The positive electrode material hydroxide precursor Ni 0.9 Co 0.05 Mn 0.05 (OH) x The temperature was heated to 800°C at a heating rate of 0.5°C / min and kept at this temperature for 10 hours for annealing. During the annealing process, the pressure of the reaction environment was controlled at 2.0 kPa to obtain an oxide precursor with the general chemical formula of Ni 0.9 Co 0.05 Mn 0.05 O x (The content deviation of each element is within ±1%).
[0234] Comparative Example 3
[0235] The difference from Example 2 is that:
[0236] (2) The positive electrode material hydroxide precursor Ni 0.67 Co 0.05 Mn 0.28 (OH) x The temperature was heated to 600°C at a heating rate of 2°C / min and annealed for 6 hours to obtain an oxide precursor with a general chemical formula of Ni 0.67 Co 0.05 Mn 0.28 O x (The content deviation of each element is within ±1%).
[0237] Comparative Example 4
[0238] The difference from Example 1 is:
[0239] (2) Placing the positive electrode material hydroxide precursor in an atmosphere with a nitric acid concentration of 2% for nitration annealing; the atmosphere contains only HNO3 and H2O, and the O2 content is <1.0ppm; heating to a temperature of 100°C at a heating rate of 2°C / min, and annealing for 2 hours; during the annealing process, the gas pressure of the reaction environment is controlled at 3.0kPa to obtain a hydroxide precursor.
[0240] Table 1 Comparison of positive electrode materials of the embodiment and the comparative example
[0241]
[0242] The button cell containing the positive electrode material was subjected to electrochemical testing, and the test results are shown in Table 2 below.
[0243] Table 2 Performance comparison of batteries of the embodiment and the comparative example
[0244]
[0245]
[0246] According to the test data of Examples 1 to 15, the present application synergistically controls the mass content of free nitrate ions and the particle size distribution of the positive electrode material, so that the positive electrode material can have both excellent structural stability and high voltage cycle stability.
[0247] According to the test data of Example 1 and Example 14, the grading frequency in the preparation process of Example 14 is relatively high, resulting in a larger particle size distribution width Span(a) of particles in the range of 1μm to 4μm. Although the compaction density of the positive electrode material is increased, the impedance between particles is increased, resulting in a slight decrease in the discharge capacity and first coulomb efficiency of the positive electrode material compared to Example 1.
[0248] According to the test data of Example 1 and Example 15, in the preparation process of Example 15, the air pressure of the airflow pulverization is low and the grading frequency is low, resulting in a decrease in the particle size distribution width Span (b) of the particles in the range of 0.1μm to 1μm, resulting in small-size particles being more concentrated. Although the compaction density of the positive electrode material is further improved, the side reactions between the positive electrode material and the electrolyte increase, which will affect the first coulomb efficiency and high-voltage cycle capacity retention rate of the positive electrode material.
[0249] According to the test data of Example 1 and Comparative Example 1, Example 5 and Comparative Example 2, and Example 2 and Comparative Example 3, Comparative Examples 1 and 2 were not subjected to nitration annealing treatment during the preparation process, and the oxide precursor of the positive electrode material did not contain free nitrate. Therefore, too little Li2O was formed on the surface of the positive electrode material, and the side reaction between the positive electrode material and the electrolyte was aggravated. In particular, under high-voltage charge and discharge conditions, the capacity loss of the positive electrode material was aggravated, and the high-voltage cycle capacity retention rate was reduced.
[0250] According to the test data of Example 1 and Comparative Example 4, the annealing temperature of the hydroxide precursor is too low during the nitric acid annealing treatment. After annealing, the precursor is still a hydroxide with a layered crystal structure. The hydroxide precursor reacts with the lithium salt, and the diffusion thermodynamic rate of lithium is faster than that of the oxide precursor. The sintered product has more uniform particle size, with only a small amount of particles with a particle size of less than 1 μm. The positive electrode material has only one characteristic peak, namely the second characteristic peak. Therefore, the compaction density of the positive electrode material decreases, resulting in a decrease in the discharge capacity, first coulomb efficiency and high voltage cycle capacity retention rate of the positive electrode material.
[0251] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A positive electrode material, characterized in that: The mass content of free nitrate ions in the positive electrode material is Q ppm, 10≤Q≤100; in the particle size number distribution spectrum of the positive electrode material, the positive electrode material has a first characteristic peak and a second characteristic peak, the first characteristic peak is located in the range of 0.1μm to 1μm and does not include 1μm, and the second characteristic peak is located in the range of 1μm to 4μm.
2. The positive electrode material according to claim 1, characterized in that The positive electrode material satisfies at least one of the following conditions: (1) The particle size number distribution width of the first characteristic peak is Span(b), which satisfies 0.4<Span(b)<0.8; (2) The particle size number distribution width of the second characteristic peak is Span(a), which satisfies 0.8<Span(a)<1.64; (3) The intensity ratio of the first characteristic peak to the second characteristic peak is ≥1.
5.
3. The positive electrode material according to claim 1, characterized in that The chemical formula of the positive electrode material is Li n Ni x M y Mn z O2, wherein 0.9≤n<1.1, 0≤y<1, 0≤z<1, x+y+z=1, and y and z are not equal to 0 at the same time, wherein the M element includes at least one of Co, Al, Zr, Mg, W, Ti, Ba, Sr, Mg, Cr, Zn, V, Cu, Nb, Mo, Y and W.
4. The positive electrode material according to claim 1, characterized in that The volume particle size distribution of the positive electrode material satisfies: 1.0 μm≤Dv10≤2.5 μm, 3.0 μm≤Dv50≤4.5 μm, 5.5 μm≤Dv90≤10.0 μm.
5. The positive electrode material according to claim 1, characterized in that The mass content of free sulfate in the positive electrode material is K ppm, 10≤K≤800.
6. The positive electrode material according to claim 1, characterized in that The positive electrode material is a single crystal material, and the positive electrode material includes crystal grains, and the grain size of the crystal grains is 1 μm to 5 μm.
7. The positive electrode material according to any one of claims 1 to 6, characterized in that: The specific surface area of the positive electrode material is 0.5 m 2 / g~1.5m 2 / g.
8. The positive electrode material according to any one of claims 1 to 6, characterized in that The positive electrode material satisfies at least one of the following conditions: (1) The tap density of the positive electrode material is 1.0 g / cm 3 ~3.0g / cm 3 ; (2) The compaction density of the positive electrode material is 2.5 g / cm 3 ~3.5g / cm 3 ; (3) The bulk density of the positive electrode material is 0.5 g / cm 3 ~1.5g / cm 3 .
9. The positive electrode material according to any one of claims 1 to 6, characterized in that The button-type battery made of the positive electrode material has a capacity retention rate of ≥95% after 50 cycles at a high voltage upper limit of 4.45V.
10. A battery, characterized in that: The battery comprises the positive electrode material according to any one of claims 1 to 9.
Citation Information
Cited By
Positive electrode material and battery
EP4769556A1
Positive electrode material and battery
WO2026057095A1